Model Pengayaan Tutor Bahasa: Studi pre-learning pada Shabahul Lughoh di Ma’had Sunan Ampel Al Aly - Nuril Mufidah; Ulya Zahrotul Firdaus; Saidna Zulfiqar Bin Tahir (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Mahad Sunan Ampel Al Aly (MSAA) is an Islamic educational institution under the auspices of the State Islamic University of Maulana Malik Ibrahim Malang. All new students are required to live in the dormitory (Mahad) for one year with the aim of creating a conducive atmosphere in the development of education, forming the character of polite students through religious activities, as well as improving language skills (Arabic and English) through linguistic activities. Musyrif (male counselor) and Musrifah (female counselor) has an essential role in achieving that goal. They are educators or tutors in scientific activities.To improve the competence of the Musrif and Musrifah in teaching, the pre-learning programs are held every once a week on weekends. This study aims to explore the model of tutor’s pre-teaching to enrich the programs of language learning activities at MSAA. The research method used is the case study method using observation and interview techniques. The results showed that the pre-learning program provided the ability of Musrif and Musrifah to organize the time appropriately, mastered sufficient material to be conveyed to new students, gained knowledge about variations and language learning games, and motivated techniques.